Pathovar specific molecular detection of Xanthomonas campestris pv. campestris, the causal agent of black rot disease in cabbage. Issue 3 (3rd July 2019) - Rubel, Mehede H.; Natarajan, Sathishkumar; Hossain, Mohammad R.; Nath, Ujjal K.; Afrin, Khandker S.; Lee, Ji-Hee; Jung, Hee-Jeong; Kim, Hoy-Taek; Park, Jong-In; Nou, Ill-Sup
Abstract: Various pathovars (pv.) of Xanthomonas campestris ( Xc ) are prevalent in South Korea, of which pv. campestris causing black rot threatens the production of cabbage in this major cabbage producing country of the world. Rapid and sensitive detection of the pathovar is an essential prerequisite for any plant protection programme. This study took an approach of re-aligning the whole genome sequences (upon availability) of representative strains of the bacteria and identified pathovar-specific genomic regions that are absent in other pathovars and other bacterial strains. Herein, eight Sequence Characterized Amplified Regions (SCAR) primer sets were designed, of which three sets, namely Xcc _48F/R, Xcc _53F/R and Xcc _79F/R, specifically amplified all Xcc strains and did not amplify other pathovars and bacterial strains. These primers also detected the Xcc strains collected from black rot infected field samples in South Korea. After optimizing the PCR conditions, one of the primers, Xcc _48F/R, was able to amplify as low as 6 × 10 −3 ng μL −1 bacterial DNA. This unique method of marker development thus yielded sensitive, specific and reliable markers that can be used for efficient and inexpensive detection of Xcc for purposes including quarantine and disease forecasting by early detection from asymptomatic field samples. Additionally, the method can be replicated in developing markers from other phyto-pathogenic agents for which the variable genomic regions are not known.